DIVERSITY AND UTILIZATION OF Dioscorea spp. TUBER AS ALTERNATIVE FOOD SOURCE IN NGANJUK REGENCY, EAST JAVA - Trimanto, Trimanto; Hapsari, Lia (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2015)
Dioscorea spp. is local tuberous food crop that has potential as alternative food source to support food security program in Indonesia. Exploration study and collecting mission subjected to Dioscorea spp. have been conducted in Nganjuk Regency. The study was aimed to 1) determine the distribution of Dioscorea spp. in Nganjuk, 2) to characterize tuberâs morphological characteristic, and 3) to know how tuberâs utilization by local peoples. The results showed that there were 4 species of Dioscorea found in Nganjuk. They are Dioscorea alata L, Dioscorea esculenta (Lour.) Burkill, Dioscorea hispida Dennst and Dioscorea bulbifera L. Dioscorea alata (uwi) is the most cultivated by farmers in Nganjuk. It has the largest cultivar numbers which Â consists of 11 cultivars. Dioscorea esculenta (gembili) consists of 3 cultivars and Dioscorea hispida (gadung) consists of 4 cultivars, whereas Dioscorea bulbifera (uwi gantung) consists only 1 cultivar in one location. Farmers and local peoples play important role in conservation of Dioscorea in Nganjuk region by cultivating and utilizing it as alternative food source for home consumption. Â Keywords: Dioscorea, diversity, food source, Nganjuk, utilization